2021
DOI: 10.1002/anbr.202100034
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Metal–Organic Frameworks at the Subcellular Level

Abstract: Organelles, or subcellular structures, are the fundamental functional units in almost all eukaryotic cells. Consequently, they play a critical role in the development of various biomedical applications, such as targeted drug delivery, biosensing, imaging, and biomimetics. Many efforts are devoted to developing nanosystems that can target specific organelles in a controlled manner. A series of nanomaterials with high porosity, stability, and easy‐to‐tailor properties, named metal–organic frameworks (MOFs), have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…38 In addition to PEM films, metal−organic frameworks (MOFs) have emerged as another cytocompatible material for cell surface modulation with potential for in situ assembly. Synthetic MOFs have been investigated extensively in the context of drug or nanomedicine delivery 39 as well as scaffolds for improving enzyme stability or function in biocatalysis. 40 More relevant to assembly in living organisms, Liang and coworkers 41 demonstrated that zeolitic-imidazolate framework-8 (ZIF-8) could be assembled on the surface of Saccharomyces cerevisiae (Figure 2c) and Micrococcus luteus, a proof-of-concept for in situ MOF assembly on living cells as a means for cytoprotection.…”
Section: Nongenetically Targeted Strategies For In Situ Synthesis And...mentioning
confidence: 99%
“…38 In addition to PEM films, metal−organic frameworks (MOFs) have emerged as another cytocompatible material for cell surface modulation with potential for in situ assembly. Synthetic MOFs have been investigated extensively in the context of drug or nanomedicine delivery 39 as well as scaffolds for improving enzyme stability or function in biocatalysis. 40 More relevant to assembly in living organisms, Liang and coworkers 41 demonstrated that zeolitic-imidazolate framework-8 (ZIF-8) could be assembled on the surface of Saccharomyces cerevisiae (Figure 2c) and Micrococcus luteus, a proof-of-concept for in situ MOF assembly on living cells as a means for cytoprotection.…”
Section: Nongenetically Targeted Strategies For In Situ Synthesis And...mentioning
confidence: 99%
“…This tunability allows for the customization of MOFs to match specific biomedical requirements, such as accommodating different‐sized molecules or targeting specific tissues or cells. [ 58 ] Encapsulation and protection of active agents: MOFs can encapsulate and protect sensitive or labile drugs or therapeutic molecules from degradation, enzymatic activity, or premature release. The porous structure of MOFs can shield the encapsulated agents from external factors, providing stability and controlled release in physiological environments.…”
Section: Fundamentals Of Mofsmentioning
confidence: 99%
“…Thus, the most promising biomedical application of these systems has been for the mapping of tumor cell biomarkers through colorimetric immunoassays [76]. This technique is efficient and enables cell cycle monitoring and cancer detection at an early stage, which has rendered it very promising in clinical screenings [118]. In addition to this, its high porosity allows for better stability in the anchoring of several bioactive elements, which can bind to the enzyme-MOF complex and be subsequently mapped by confocal microscopy.…”
Section: Mof-based Electrochemical Biosensors For Detecting Cancer Biomarkersmentioning
confidence: 99%